Thoracic Surgery Preparation, Patient Election, and Its Management During Covid-19 Pandemic: Surabaya Experiences - Laksono, Gerardo AK; Hutama, Andreas MS; Tahalele, Paul L (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
A novel coronavirus pneumonia outbreak began in Wuhan, Hubei Province, in December 2019. It has spread rapidly from China to worldwide. The COVID-19 pandemic of 2020 posed a historic challenge to health care systems around the world, healthcare systems needed to consider providing clinical services to other patients in need. The specialty of general thoracic surgery includes the management of serious diseases such as chest wall congenital anomaly, lung cancers, esophageal cancers, mediastinal tumor, chest wall infection, and trauma. Thoracic surgery is one of high risk procedure in this pandemic, however, a high level of evidence supports the surgical management of potential patients with thoracic disease and anomaly is still lacking. Critical determinants of robust thoracic surgery service provision are pre-existing plans for epidemic response.